Surviving the edge: Strategies for maximizing recovery in near-hanging cases: A case series - Arvind Kumar Yadav; Suhas Kumar Mall; Vempalli Nagasubramanyam; Rahul Gupta; Arun Kumar Pandey; Konda Sireesha (Journal of Family Medicine and Primary Care)
Hanging is a common method of suicide/homicide in India. We report a series of three cases of suicidal hangings and one accidental strangulation case seen over 4 months in the Department of Trauma and Emergency Medicine. All our patients presented in very critical condition and were treated with early aggressive management resulting in excellent outcomes.